Job satisfaction for Horeca staff in the current pandemic context - Sandu, Mihaela Luminița; Rus, Mihaela; Robu, Ruxandra Elena; Neacșu, Loredana (Technium Social Sciences Journal, 2022)
This study discusses the effects of the Covid-19 pandemic on the HoReCa industry and how it has affected employee job satisfaction. Job satisfaction is a positive emotional state that consists of the employee's personal opinion on personal work or work climate, a state of equity that the individual reaches when he fully meets certain needs or expectations. In this study, we wanted to see exactly how the pandemic affected the employees and their job satisfaction by giving them questionnnaires that evaluate their satisfaction in the current situation.The study found that there was no significant difference between women and men in terms of job satisfaction, that there was no correlation between education level and job satisfaction and that there was no correlation between the position held in the hierarchy and job satisfaction.The current pandemic context has affected many HoReCa employees due to the fact that they can no longer operate due to the closure of restaurants, bars, limiting tourist access to hotels. Thus, job satisfaction is low because the quality of the job has also decreased.The Horeca sector is particularly fragile and vulnerable to economic cycles and shocks, as the current health pandemic has shown.The study also had a number of limitations imposed by the online evaluation method, the generalization of the results and the experience of the participants.